2016
DOI: 10.1038/ncomms10230
|View full text |Cite
|
Sign up to set email alerts
|

Periprostatic adipocytes act as a driving force for prostate cancer progression in obesity

Abstract: Obesity favours the occurrence of locally disseminated prostate cancer in the periprostatic adipose tissue (PPAT) surrounding the prostate gland. Here we show that adipocytes from PPAT support the directed migration of prostate cancer cells and that this event is strongly promoted by obesity. This process is dependent on the secretion of the chemokine CCL7 by adipocytes, which diffuses from PPAT to the peripheral zone of the prostate, stimulating the migration of CCR3 expressing tumour cells. In obesity, highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(216 citation statements)
references
References 66 publications
7
205
2
2
Order By: Relevance
“…For ex am ple, stroma as so ci ated pan cre atic stel late cells (my ofi brob last like cells) pro duce non es sen tial amino acids, in par tic u lar ala nine that sup port pan cre atic tu mor me tab o lism [96]. In an other ex am ple, adipocytes, which are abun dant in the tu mor mi croen vi ron ment of re nal, breast, prostate and ovar ian can cers and have been for long con sid ered as pas sive by standers to can cer de vel op ment [97][98][99], usu ally dis play fewer lipid droplets com pared to nor mal adipocytes, sug gest ing that they sup ply fatty acids to nearby can cer cells [78]. Nie man et al [99] showed that hu man omen tal adipocytes pro mote the in va sion, mi gra tion and metas ta sis of SKOV3ip1 hu man ovar ian can cer cells to ward the omen tum.…”
Section: Metabolic Cooperation In Cancermentioning
confidence: 99%
“…For ex am ple, stroma as so ci ated pan cre atic stel late cells (my ofi brob last like cells) pro duce non es sen tial amino acids, in par tic u lar ala nine that sup port pan cre atic tu mor me tab o lism [96]. In an other ex am ple, adipocytes, which are abun dant in the tu mor mi croen vi ron ment of re nal, breast, prostate and ovar ian can cers and have been for long con sid ered as pas sive by standers to can cer de vel op ment [97][98][99], usu ally dis play fewer lipid droplets com pared to nor mal adipocytes, sug gest ing that they sup ply fatty acids to nearby can cer cells [78]. Nie man et al [99] showed that hu man omen tal adipocytes pro mote the in va sion, mi gra tion and metas ta sis of SKOV3ip1 hu man ovar ian can cer cells to ward the omen tum.…”
Section: Metabolic Cooperation In Cancermentioning
confidence: 99%
“…In cell line models, lipids taken up by prostate cancer cells can drive proliferation (Nieman et al 2013) and potentially invasiveness (Sacca et al 2012). Moreover, a recent report has demonstrated enhanced migration of prostate cancer cells induced by coculture with periprostatic-derived adipocytes from obese compared with lean mice (Laurent et al 2016). Given that the antitumor effects of inhibiting lipogenesis can be overcome by providing exogenous fatty acids (Kuemmerle et al 2011, Griffiths et al 2013, uptake of fatty acids by prostate tumor cells may be an important mechanism of clinical resistance to inhibitors of lipid synthesis (e.g.…”
Section: Androgens Stimulate Lipid Synthesis Uptake and Storagementioning
confidence: 99%
“…The crosstalk between fat cells and cancer cells plays an important role in driving cancer survival and metabolism for several tumor types such as ovarian, breast, prostate and pancreatic cancers. [1][2][3] This is particularly important in the case of ovarian cancer since, unlike other tumors, it rarely metastasizes outside the abdominal cavity. The main cause of death from ovarian cancer is malnutrition secondary to intestinal obstruction because of metastasis-induced adhesion formation.…”
Section: Editorials: Cell Cycle Featuresmentioning
confidence: 99%